Agency in Computer-Assisted Language Learning (CALL): Learning to Use Language for a Sustainable Post-COVID-19 Society - Hussain, Riaz; Ilyas, Usman; Ilyas, Aisha (Sustainable business and society in emerging economies, 2021)
Purpose: Against a background of educational world hampered by the pandemic of COVID-19, the current study aimed to explore ESL learners’ perceptions about the potential of Computer-Assisted Language Learning in helping them create and share knowledge for a sustainable Post-COVID-19l society. Design/Methodology/Approach: The current study followed Quantitative approach with exploratory research design. A close- ended questionnaire designed and piloted by the researches was distributed among 100 ESL learners pursuing their studies at the department of English, the Islamia university of Bahawalpur and the department of English, the Government Sadiq Egerton College Bahawalpur. Findings: The findings of the study reveal that 71% of the respondents are not aware of the novel concept of ‘agency’ in Computer Assisted Language Learning (CALL) and education. However, the results show that 80% of the respondents are aware of the importance of the ESL learners making linguistic, communicative and interactive contributions in real life and the potential of computer technology for sustainable L2 development. Implications/Originality/Value: In Pakistan there have been done few studies on the aspect of “agency” in Computer Assisted Language Learning (CALL). The findings imply that since most of the learners are unaware of the concept of “agency” in CALL, therefore, ESL teachers should acquaint ESL learners not only with the dynamic concept but also with the novel practical applications of the concept.